STRATEGI PEMBERITAAN MEDIA ONLINE INDONESIA DALAM KASUS DEMONSTRASI RUU HIP (ANALISIS WACANA KRITIS THEO VAN LEEUWEEN) - Mclean HY (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2022)
This research aimedto describe the different points of view among the Indonesian national online media, namely Detiknews.com, Kompas.com, CNN Indonesia and Tempo.com and to describe the tendency of the online media's attitudes in constructing the Demonstration case of the RUU HIP. The exclusion strategy is used to see how actors are excluded or hidden in the news text. This exclusion and inclusion strategy looks at how the forms of language usage are used to recapture the meaning to the public. The data of this research were found from reporting on the demonstration case of the RUU HIP in July 2020 in online media Detiknews.com, Kompas.com, Tempo.com and CNN Indonesia during 15-16 July 2020. This research used a qualitative descriptive method with a critical discourse analysis by Theo Van Leeuwen in order to describe how events and actors are portrayed in the news. The results showed that the form of Leeuwen's exclusion theory found in four news reports in online media was that Detiknews.com, Kompas.com, and CNN Indonesia in the news about the demonstration of the RUU HIP tended to use an inclusion strategy while, Tempo.com was more towards exclusion